Comparative study of intermetallic compound formation in Sn-Ag-Cu and eutectic Sn-Pb solders on bare copper and electroless nickel immersion gold (ENIG) substrates - Mechilina, Aurelia Celebre
The introduction of lead free materials (Sn-Ag-Cu solder in this study) in electronic packaging gives rise to new problems on the reliability of the solder joints since the addition of other constituents (Ag and Cu) plus the higher Sn content of the solder contribute to intermetallic precipitation in the solder and at the interafaces. These precipitates will significantly affect the mechanical properties of the solder joint and the formation of intermetallics at the interface. This research is a comparative study of the intermetallic formation at the solder-substrate interface using eutectic (63wt% Sn- 37 wt% Pb) and leadfree (95.5wt Sn-4wt Ag-0.5wt Cu) solders reflowed in air and mounted on Electroless Nickel Immersion Gold (ENIG) and bare copper (Cu) substrates using the JEM410 IR Convection reflow oven. Considering the melting points of the solders in degrees Centigrade, the samples were thermally aged at 0.6Tm (this corresponds to actual temperatures of 110 degree celcius and 132 degree celcius for Sn-Pb and lead free solders, respectively) and 0.8Tm (146 degree celcius and 176 degree celcius for Sn-Pb and lead free solders, respectively) for 8 and 16 days. The intermetallic compound (IMC) formation, microstructures and elements present at the interface were observed by SEM-EDX analysis and the intermetallic layer thickness quantitatively estimated using image analysis software. Statistical analysis of the results showed significant interactions between the type of solder and type of substrate, type of solder and aging temperature and type of substrate and aging temperature at the 95% confidence level. Varying the aging time from 8 to 16 days did not show a significant effect on intermetallic layer thickness at the 95% confidence level. The interaction plots showed that lesser intermetallic layer formation was favored using eutectic Sn-Pb solder rather than lead free solder, ENIG substrate and lower aging temperature. These effects are attributed to the lower Sn content of the eutectic Sn-Pb solder, the barrier effect provided by the ENIG layer to interdiffusion of Cu and Sn, and the lower diffusion rates expected at lower temperature. Considering the data from aging times of 0 to 16 days, the chemical reaction controlled kinetics model had better fit for 0.6Tm data (based on R2 criterion) while the product layer diffusion controlled kinetics model showed better fit for 0.8 Tm data. The equivalent aging times needed to produce the initial intermetallic layer thickness values produced by the reflow step were also estimated by extrapolation of linear functions to zero thickness. Comparison of the thickness of intermetallic layers produced right after reflow with the values measured after the maximum aging time of 16 days revealed that the intermetallic thickness corresponding to the transition from chemical reaction controlled kinetics to product layer diffusion controlled kinetics appears, in general, to be in the vicinity of 2.1 um.